Religion and Humanity: A Southeast Asian Perspectives - Nikmah, Faridatun; Pramitha, Devi; Anggarini, Ida Fitri; Noviyanti, Shobihatul Fitroh (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Religion and humanity are a crucial topic. RelSoutheast humanity has been implemented in Southeast Asia, especially for school education or community life. This study aims to discover Southeast Asian perceptions toward food and humanity. A qualitative descriptive design was employed for this study. The data were gathered through virtual in-depth interviews with six Southeast from Indonesia, Malaysia, Philippines, Thailand, Laos, and Vietnam. Thematic analysis was used to analyze the research data. The findings revealed three points related to Religion and humanity: (1) the urgency of Religion and humanity, (2) factors improving humanity, and (3) barriers.